A New Benzoyl Compound Isolated from the Endophytic Fungi of Kandis Gajah (Garcinia griffithii) and Asam Kandis (Garcinia cowa) - Elfita,; Munawar,; Muharni,; Pratiwi, Gusti; Rahmadania, (Makara Journal of Science, 2016)
Garcinia griffithii and Garcinia cowa belong to the genus Garcinia. The genus Garcinia has been known to be a rich source of secondary metabolites, such as xanthones, benzophenones, flavonoids, steroids, terpenoids, and other phenolic derivatives. Previous investigations of endophytic fungi from G. griffithii revealed the presence of three compounds not found in the host. In order to the continue the phytochemical work on endophytic fungi of G. griffithii, the constituent of the endophytic fungi of G. griffithii was re-examined. In this study, a benzoyl compound similar to that found in the endophytic fungus of G. cowa was observed. The same benzoyl compound was also isolated from the endophytic fungus Acremonium sp of G. griffithii and Aspergillus sp of G. cowa with cultivation of eight weeks in static conditions at room temperature. The culture medium was partitioned using ethyl acetate and evaporated to obtain the concentrated extract. Isolation of compounds was performed using the chromatography method. The chemical structure was proposed on the basis of spectroscopic data, including ultraviolet (UV), infrared (IR), mass spectrometry (MS), proton nuclear magnetic resonance ( 1H-NMR), carbon nuclear magnetic resonance ( 13C-NMR), heteronuclear single-quantum correlation spectroscopy (HSQC), heteronuclear multiple-bond correlation spectroscopy (HMBC), and correlation spectroscopy (COSY).